Lean PLM - Information Technology Strategy for Innovative and Sustainable Business Environment - Gecevska, Valentina; Veza, Ivica; Cus, Franc; Anisic, Zoran; Stefanic, Nedeljko (International Journal of Industrial Engineering and Management, 2012)
In today’s process manufacturing environment, innovation is viewed as critical to sustainable growth and business profitability. While innovation is regarded as the answer, the companies can effectively measure the return on R&D investment, have acceptable product success rates, achieve acceptable promotional effectiveness, or have visibility into their compliance risks or operational readiness for new product launches. Companies must have repeatable, compliant and responsive business processes, global ICT information infrastructure that provides a single source of the truth, alignment across departments and solutions that evolve without coding. With holistic strategy and supporting infrastructure, companies can consistently minimize the time to scale, improve product success rates and promotional effectiveness, and enjoy sustainable and profitable growth. The companies must first focus on the needs of their customer, continually minimize time to scale, eliminate waste, drive out costs and improve. These are core concepts of a Lean strategy. This paper will describe how Lean concept with PLM business strategy can leverage Lean with integrated compliance, continual improvement and other PLM best practices to increase the return on R&D investments and provide sustainable and profitable growth for business processes mainly manufacturing processes. The purpose of this paper is to review PLM approach linked to Lean concepts in order to achieve sustainable and innovative business environment with profitable growth. Article history: Received (18 December 2011); Revised (17 January 2012); Accepted (27 January 2012)